The EFL Students’ Perception of the Online Learning during Covid-19 Pandemic and New Normal Era - Khadijah Maming; Widya Rizky Pratiwi; Ali Wira Rahman; Muh. Bustamin Khaldun (Hasanuddin University, 2023)
This research aimed to investigate the EFL students’ perception and expectation of the online learning of the online learning during Covid-19 pandemic and new normal era. This research applied quantitative and qualitative descriptive with survey method. The participants were the English education study program students consisting of fifteen participants at Universitas Muhammadiyah Parepare. In this research, the researchers conducted interview and questionnaire to obtain the data. The result of this research showed that online method was the best solution to be applied change the offline class based on the condition nowadays, but still ineffective in the application. Another result showed that in the implementation of online learning during this pandemic era there was some obstacles found and need more improvement to make learning process more effective. In brief, online learning is relatively good with several obstacles that require improvement. Thus, it is recommended to create a good learning platform that can be applicable in current situation. So that, it is recommended that online learning should be planned, implemented, and evaluated to minimize problems and maximize the achievement of learning objectives.